Investigation of Caputo proportional fractional integro-differential equation with mixed nonlocal conditions with respect to another function - Khaminsou, Bounmy; Sudsutad, Weerawat; Kongson, Jutarat; Nontasawatsri, Somsiri; Vajrapatkul, Adirek; Thaiprayoon, Chatthai (AIMS mathematics, 2022)
In this manuscript, we analyze the existence, uniqueness and Ulam's stability for Caputo proportional fractional integro-differential equation involving mixed nonlocal conditions with respect to another function. The uniqueness result is proved via Banach's fixed point theorem and the existence results are established by using the Leray-Schauder nonlinear alternative and Krasnoselskii's fixed point theorem. Furthermore, by using the nonlinear analysis techniques, we investigate appropriate conditions and results to study various different types of Ulam's stability. In addition, numerical examples are also constructed to demonstrate the application of the main results.